Soluble Urokinase‐Type Plasminogen Activator Receptor and High‐Sensitivity Troponin Levels Predict Outcomes in Nonobstructive Coronary Artery Disease. Issue 8 (21st April 2020) - Al‐Badri, Ahmed; Tahhan, Ayman Samman; Sabbak, Nabil; Alkhoder, Ayman; Liu, Chang; Ko, Yi‐An; Vaccarino, Viola; Martini, Afif; Sidoti, Arianna; Goodwin, Cydney; Ghazzal, Bahjat; Beshiri, Agim; et al.
Abstract : Background: Multiple biomarkers have been independently and additively associated with major adverse cardiovascular events in patients with coronary artery disease. We investigated the prognostic value of suPAR (soluble urokinase‐type plasminogen activator receptor) and hsTnI (high‐sensitivity troponin I) levels in symptomatic patients with no obstructive coronary artery disease. We hypothesized that high levels of these biomarkers will be associated with the risk of future adverse outcomes. Methods and Results: Plasma levels of suPAR and hsTnI were measured in 556 symptomatic patients with no obstructive coronary artery disease. A biomarker risk score was calculated by counting the number of biomarkers above the median in this cohort (suPAR>2523 pg/mL and hsTnI>2.7 pg/mL). Survival analyses were performed with models adjusted for traditional risk factors. All‐cause death and major adverse cardiovascular events (cardiovascular death, myocardial infarction, stroke, and heart failure) served as clinical outcomes over a median follow‐up of 6.2 years. Mean age was 57±10 years, 49% of the cohort patients were female, and 68% had a positive stress test. High suPAR and hsTnI levels were independent predictors of all‐cause death (hazard ratio=3.2 [95% CI, 1.8–5.7] and 1.3 [95% CI, 1.0–1.7], respectively; both P <0.04) and major adverse cardiovascular events (hazard ratio=2.7 [95% CI, 1.4–5.4] and 1.5 [95% CI, 1.2–2.0], respectively; both P <0.002). Compared with a biomarker risk score of 0, biomarker risk scores of 1 and 2 were associated with 19‐ and 14‐fold increased risk of death and development of major adverse cardiovascular events, respectively. Conclusions: Among symptomatic patients with no obstructive coronary artery disease, higher levels of suPAR and hsTnI were independently and additively associated with an increased risk of adverse events. Whether modification of these biomarkers will improve risk in these patients needs further investigation.